Holocene hydroclimate variability along the Southern Patagonian margin (Chile) reconstructed from Cueva Chica speleothems - Nehme, C.; Todisco, D.; Breitenbach, S. F. M.; Couchoud, I.; Marchegiano, M.; Peral, M.; Vonhof, H.; Hellstrom, J.; Tjallingii, R.; Claeys, P.; Borrero, L.; Martin, Fabiana Maria (My University, 2023)
Patagonia is ideally situated to reconstruct past migrations of the southern westerly winds (SWWs) due to its southerly maritime location. The SWWs are an important driver of Southern Ocean upwelling and their strength and latitudinal position changed during the Holocene, leading thus to different responses of the vegetation to past climate changes along the Chilean continental margin. A new speleothem record from Cueva Chica (51 degrees S) is investigated to reconstruct past climatic changes throughout the Holocene in conjunction with other marine and paleoenvironmental records of the region and better constrain the regional paleoclimatic evolutions of SWWs. Samples comprising both a flowstone core and a stalagmite were radiometrically dated (U-Th & 14C) to construct age-depth models for the highly-resolved proxy profiles (delta 13C, delta 18O, chemical composition). The Cueva Chica record provides a highly-resolved isotopic and elemental curves for the last 12 ka, albeit with a hiatus from 5.8 to 4 ka BP. The multi-proxy analysis suggests three climatic regimes throughout the Holocene in Southern Patagonia: i) an early Holocene wet period (with the exception of two dry excursions at 10.5 ka and 8.5 ka BP), ii) a mid-Holocene dry period and iii), a return to generally wet conditions over the late Holocene. The global drivers for these tri-phased climatic regimes are likely related to oceanic and South polar feedbacks. The early Holocene was the warmest period and might be attributable to changes in global ocean circulation which involved a rise in air T degrees and a strength in SWW from 50 degrees S, and therefore higher precipitations over landmass. After 9 ka BP, an intensified deglaciation dynamic along the Antarctic Peninsula is concordant with increasing summer insolation in the Southern hemisphere, leading to a poleward shift of the SWWs in response to global warming and thus to a reduction in moisture supply from the Pacific onto the Patagonian shore. After 5 ka BP, a gradual SST decline is consistent with an equatorward shift of the SWWs in response to a cooling Southern hemisphere. The SWW storm tracks extended to lower latitudes, inducing a return to wetter conditions with highly variable moisture patterns along the Patagonian landmass. Clumped isotope (Delta 47) analyses at lower resolution reflect the degree of kinetic isotope fractionation at the time of carbonate deposition, especially during the dry interval around 8.5-5.5 ka BP. Reduced kinetic isotope fractionation is observed since at least 2.6 ka BP, a period marked by (slightly) wetter conditions.
Keywords: patagonia; holocene; speleothems; stable isotopes; southern westerly winds